A mutation in the Z‐line Cypher/ZASP protein is associated with arrhythmogenic right ventricular cardiomyopathy. (8th September 2014) - Lopez‐Ayala, J. M.; Ortiz‐Genga, M.; Gomez‐Milanes, I.; Lopez‐Cuenca, D.; Ruiz‐Espejo, F.; Sanchez‐Munoz, J. J.; Oliva‐Sandoval, M. J.; Monserrat, L.; Gimeno, J. R.
<x xml:space="preserve">Abstract</x> Arrhythmogenic right ventricular cardiomyopathy (ARVC) is an important cause of malignant arrhythmia and sudden death particularly in young people. Although it is considered a desmosomal disease, mutations in non‐desmosomal genes have also been identified. We report on a family where a mutation in LDB3 is associated with this condition. The index case and first and second degree relatives underwent a complete clinical evaluation: physical examination, electrocardiography (ECG), signal‐averaged ECG, 2D echocardiogram, cardiac magnetic resonance and 24‐h monitoring. After ruling out mutations in the five desmosomal genes, genetic testing by means of Next Generation Sequencing was carried out on the proband. A heterozygous missense mutation in LDB3 c.1051A>G was identified. This result was confirmed by subsequent Sanger DNA sequencing. Another six carriers were identified amongst her relatives. Three subjects fulfilled the criteria for a definitive diagnosis of ARVC and one reached a borderline diagnosis. In conclusion, this is the first family with ARVC where a mutation in LDB3 is associated with ARVC. Next generation sequencing arises as a particular useful tool to point to new causative genes in ARVC.